Pengaruh Talent Management, Knowledge Management, Pelatihan, Motivasi dan Kompensasi Terhadap Kinerja Karyawan di Kota Batam Pada Sektor Perbankan - Darvin, Darvin; Setyawan, Agustinus (REVITALISASI : Jurnal Ilmu Manajemen, 2024)
This research aims to analyze the influence of talent management, knowledge management, training, motivation and resolution on employee performance in the city of Batam in the banking sector. The research method carried out by researchers uses quantitative methods. The objects of this research are banking employees in the city of Batam. The sample in this study amounted to 402 respondents using the SPSS application. The research results showed that all variables were found to be significantly positive on employee performance.